Rolling in the Deep: Imaging Findings and Diagnostic Pearls in Gallstone Ileus. (24th April 2020) - Aldo, Carnevale; Lorenzo, Motta; Olgerta, Labaj; Alberto, Cossu; Licia, Uccelli; Melchiore, Giganti
Abstract : Gallstone ileus is a dramatic complication of gallstone disease, uncommon but not exceptional in a busy emergency department. It represents a cause of mechanical intestinal obstruction, which predominantly occurs in elderly and frail patients; this contributes to the high morbidity and mortality rates associated with this condition. The modern radiologist is frequently asked to determine the cause of bowel obstruction and should be aware of the most pictorial features of this unusual disease. Broadly speaking, abdominal radiography and ultrasonography alone are limited in detecting the cause of bowel obstruction, but the sensitivity for the preoperative diagnosis of gallstone ileus may be improved by combining the findings obtained by both techniques. Computed tomography is the modality of choice for the diagnosis of this disease: it may accurately describe the number, size, and location of migrated gallstones and the exact site of bowel obstruction, providing a detailed preoperative planning. Magnetic resonance imaging may be used in selected cases for an exquisite anatomic definition of the fistulous communication.